2023
DOI: 10.1111/bph.16260
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of the integrated stress response accelerates disease progression in an amyotrophic lateral sclerosis mouse model

Elías Marlin,
Miguel Valencia,
Nuria Peregrín
et al.

Abstract: Background and PurposeThe integrated stress response (ISR) regulates translation in response to diverse stresses. ISR activation has been documented in amyotrophic lateral sclerosis (ALS) patients and ALS experimental models. In experimental models, both ISR stimulation and inhibition prevented ALS neurodegeneration; however, what mode of ISR regulation would work in patients is still debated. We previously demonstrated that the ISR modulator ISRIB (an eIF2B activator) enhances survival of neurons expressing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…This is supported by studies showing that loss of GADD34 enhances survival and delays neurodegeneration in various ALS model systems, and loss of PERK accelerates disease progression, while pharmacologically upregulating heat shock and unfolded protein response pathways significantly improves outcomes in ALS models (Ahmed et al 2023;Saxena, Cabuy, and Caroni 2009;Wang, Popko, andRoos 2011, 2014;Das et al 2015;Ghadge et al 2020). A more recent study has also shown that ISR inhibition via eIF2B activators enhances disease progression in ALS models (Marlin et al 2023). In the context of our own work, these studies support a predominantly protective role for the integrated stress response in neurodegeneration.…”
Section: Discussionmentioning
confidence: 83%
“…This is supported by studies showing that loss of GADD34 enhances survival and delays neurodegeneration in various ALS model systems, and loss of PERK accelerates disease progression, while pharmacologically upregulating heat shock and unfolded protein response pathways significantly improves outcomes in ALS models (Ahmed et al 2023;Saxena, Cabuy, and Caroni 2009;Wang, Popko, andRoos 2011, 2014;Das et al 2015;Ghadge et al 2020). A more recent study has also shown that ISR inhibition via eIF2B activators enhances disease progression in ALS models (Marlin et al 2023). In the context of our own work, these studies support a predominantly protective role for the integrated stress response in neurodegeneration.…”
Section: Discussionmentioning
confidence: 83%
“…While our results agree with other in vitro models that eIF2B activators such as ISRIB ameliorate ALS phenotypes, we also acknowledge that their effect in vivo require more investigation into the mechanism of action and side effects, given the reported data on aggravation and acceleration of disease progression. [33][34][35] Moreover, our results elucidate the biology underlying the defect allowing for alternative therapeutic approaches to be developed targeting these dysfunctional pathways.…”
Section: Discussionmentioning
confidence: 83%
“…32 Since then, a study showed ISRIB rescuing ER stress caused by SOD1 in culture, however a more recent study described ISRIB-like compounds have the ability to anticipate disease onset and thus shorten SOD1 mice lifespan. [33][34][35] Consequently, this lack of consensus in the literature underscores the need for studies in patient derived-cells. While our results agree with other in vitro models that eIF2B activators such as ISRIB ameliorate ALS phenotypes, we also acknowledge that their effect in vivo require more investigation into the mechanism of action and side effects, given the reported data on aggravation and acceleration of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that ISRIB acts allosterically to stabilize an active conformation of eIF2B that is resistant to p-eIF2α, thus inhibiting the downstream effects of p-eIF2α and reversing translational attenuation [ 90 ]. Recently, compounds 2BAct and PRXS571 were synthesized as novel selective eIF2B activators with the ability to cross the BBB [ 91 , 92 ]. Moreover, 2BAct exhibits suitability for oral administration with diet, allowing for its simple long-term application [ 92 ].…”
Section: The Perk Pathway In Ischemic Strokementioning
confidence: 99%
“…Moreover, 2BAct exhibits suitability for oral administration with diet, allowing for its simple long-term application [ 92 ]. Notably, it has been shown that ISRIB, 2BAct, and PRXS571 alleviate ER stress-induced translational inhibition without affecting ATF4 expression [ 91 ]. A recent rat study used a multiple treatment regimen to evaluate ISRIB in stroke, with the first dosing at 3 h post 90-minitue MCAO, followed by three additional doses with a 12 h interval between each dose.…”
Section: The Perk Pathway In Ischemic Strokementioning
confidence: 99%